1986
DOI: 10.1007/bf02907321
|View full text |Cite
|
Sign up to set email alerts
|

Crossing over in the male mouse as analysed by recombination nodules and bars

Abstract: The present study of 26 serially sectioned mouse spermatocyte nuclei has permitted the following observations and conclusions: l) The pachytene stage can be subdivided into an early, a mid, and a late substage. 2) A morphological change of the early spheric recombination nodule to an elongated bar is observed.3) The number of recombination structures per nucleusdecreases from a mean of 31 nodules and 2 bars at early pachytene to a mean of 8 nodules and 6 bars at mid pachytene. The number of nodules and bars re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
(47 reference statements)
3
11
0
Order By: Relevance
“…In doing so, we wished to investigate the frequency of occurrence of spermatocytes at the bouquet stage, as nuclei with large chromocenters which were noted in the Giemsa analysis of Atm Ϫ/Ϫ testes suspensions (data not shown) suggested the association of proximal chromosome ends. In normal mouse meiosis, the transient formation of a chromosomal bouquet during leptotene/zygotene discloses such nuclei at a low frequency, even in tissue sections (25,75). In accordance with these observations, SCP3 staining of undisrupted control spermatocytes revealed that all of 226 nuclei showed chromosome ends scattered over the nuclear periphery.…”
Section: Spermatogenesis Is Arrested In Prophase I In Atmsupporting
confidence: 77%
See 1 more Smart Citation
“…In doing so, we wished to investigate the frequency of occurrence of spermatocytes at the bouquet stage, as nuclei with large chromocenters which were noted in the Giemsa analysis of Atm Ϫ/Ϫ testes suspensions (data not shown) suggested the association of proximal chromosome ends. In normal mouse meiosis, the transient formation of a chromosomal bouquet during leptotene/zygotene discloses such nuclei at a low frequency, even in tissue sections (25,75). In accordance with these observations, SCP3 staining of undisrupted control spermatocytes revealed that all of 226 nuclei showed chromosome ends scattered over the nuclear periphery.…”
Section: Spermatogenesis Is Arrested In Prophase I In Atmsupporting
confidence: 77%
“…Hence, it appears that the timing and occurrence of chromosome polarization are altered in Atm Ϫ/Ϫ mice, since such an arrangement is rarely seen in pachytene spermatocytes of normal mice ( Fig. 3b and c) (25).…”
Section: Spermatogenesis Is Arrested In Prophase I In Atmmentioning
confidence: 96%
“…ATM function has been shown to influence telomere metabolism in human systems (84), and telomere sequences are aberrantly associated with the nuclear matrix (85). Similar observations have been made in spermatocytes I of Atm Ϫ/Ϫ mice, which also display an elevated frequency of nuclei with a bouquet topology (65)-a nuclear organization motif which is rarely found in wild-type mouse spermatocytes (32,79) and oocytes (87). The high frequency of bouquet cells encountered in the Atm Ϫ/Ϫ single-knockout mouse (65; this report) is further elevated in Atm-p53 doubleknockout mouse testes.…”
Section: Discussionmentioning
confidence: 61%
“…In both man and mouse about 75 per cent of XY SCs contain usually just one RN at pachytene (Hoim and Rasmussen, 1983;Glamann, 1986) whereas cytological, genetical and molecular studies of XY recombination seems to indicate obligate single crossovers in these bivalents (Evans et al, 1982;Keitges et al, 1985;Rouyer et a!., 1986). These discrepancies may be attributed either to transience of RNs (Glamann, 1986) or to absence of recombination in about 25 per cent of XY pairs, resulting in univalence (Hulten, 1974) which in turn results in spermatocyte degeneration (Burgoyne and Baker, 1984).…”
Section: Rns In No Bivalentsmentioning
confidence: 99%
“…These discrepancies may be attributed either to transience of RNs (Glamann, 1986) or to absence of recombination in about 25 per cent of XY pairs, resulting in univalence (Hulten, 1974) which in turn results in spermatocyte degeneration (Burgoyne and Baker, 1984). The A. fistulosum comparison presented in this paper shows many parallels with these studies, and shows that the correspondence of late RNs to genetical recombination extends to a relatively short region within a very large chromosome.…”
Section: Rns In No Bivalentsmentioning
confidence: 99%